Tingkat Pengetahuan, Sikap Merokok dan Nicotine Gum Therapy pada Mahasiswa Universitas Kristen Satya Wacana - Kusfindyasmoro, Catur Estiawan; Wahyudi, Andrey (Indonesian Journal of Pharmacy and Natural Product, 2022)
Cigarettes are cylinders made of paper containing chopped tobacco leaves. Nicotine Replacement Therapy is a therapy used to help smokers to quit smoking. The purpose of the study was to examine the level of knowledge, smoking attitudes and nicotine gum therapy in Satya Wacana Christian University students. The research method used is a non-experimental quantitative method using analytical descriptive methods. Respondents in the study were Satya Wacana Christian University Psychology Study Program students semester III, VI and IX totaling 67 students. Prospective data collection. The results of this study were the results of the validity test of the questionnaire on the level of knowledge, smoking attitudes and nicotine gum therapy on Satya Wacana Christian University students. Stating that all question variables are valid. Based on the reliability test of the questionnaire, the level of knowledge, smoking attitude and nicotine gum therapy obtained a value of > 0.60 which means that the questionnaire is reliable. The level of knowledge of smoking and nicotine gum therapy was found to be 71.84% with a fairly good level of knowledge category, the level of smoking attitude and nicotine gum therapy obtained results of 51.84% with a category of poor attitude level.The level of knowledge of smoking and nicotine gum therapy was found to be 71.84% with a fairly good level of knowledge category, the level of smoking attitude and nicotine gum therapy obtained results of 51.84% with a category of poor attitude level.ABSTRAKRokok merupakan silinder yang terbuat dari kertas berisi daun tembakau yang telah dicacah. Nicotine Replacement Therapy adalah terapi yang digunakan untuk membantu perokok untuk berhenti merokok. Tujuan penelitian untuk menganalisis tingkat pengetahuan, sikap merokok dan nicotine gum therapy pada mahasiswa Universitas Kristen Satya Wacana. Metode penelitian yang digunakan adalah metode kuantitatif non eksperimental menggunakan metode deskriptif analitik. Responden pada penelitian yaitu mahasiswa Universitas Kristen Satya Wacana Prodi Psikologi semester III, VI dan IX berjumlah 67 mahasiswa. Pengambilan data secara prospektif. Hasil penelitian ini adalah uji validitas kuesioner tingkat pengetahuan, sikap merokok dan nicotine gum therapy pada mahasiswa Universitas Kristen Satya Wacana menyatakan bahwa semua variabel pertanyaan valid. Berdasarkan uji reliabilitas kuesioner tingkat pengetahuan, sikap merokok dan nicotine gum therapy memperoleh nilai >0,60 yang menyatakan bahwa kuesioner tersebut reliabel. Tingkat pengetahuan merokok dan nicotine gum therapy didapatkan hasil 71,84% dengan kategori tingkat pengetahuan cukup baik, tingkat sikap merokok dan nicotine gum therapy memperoleh hasil sebesar 51,84% dengan kategori tingkat sikap kurang baik.Tingkat pengetahuan merokok dan nicotine gum therapyyaitu 71,84% dengan kategori tingkat pengetahuan cukup baik, Tingkat Sikap merokok dan nicotine gum therapyyaitu sebesar 51,84% dengan kategori tingkat sikap kurang baik.